Modification Of Star Fruit Wuluh (Averrhoa Bilimbi L.) As A Substitute For Turk Solution In The Manual Method Leukocyte Count. - Selda Lemriani Manullang; Vincentia Ade Rizky; Asvia Rahayu (Institut Kesehatan Medistra Lubuk Pakam, 2025)
Background: This study counts the number of leukocytes using a manual method. The natural materials used are lime, lemon, and tamarind, which contain glacial acid and citric acid with a pH below 2.0. These acids can lyse blood cells, except for leukocytes (white blood cells). Objective: This study aims to analyze the effectiveness of varying concentrations of starfruit (Averrhoa bilimbi) on the number of leukocytes (white blood cells). Method: This research employs an experimental method. The number of leukocytes is counted from the juice of starfruit at concentrations of 5% and 10%. The objective is to find the most effective concentration compared to the standard Turk solution as a control. Conclusion: The data were analyzed using One-Way ANOVA. The average number of leukocytes in the control group was 6,500, in the 10% concentration was 6,450, and in the 5% concentration was 4,500. The results of statistical tests and hypotheses showed a significance value of 0.000, which is less than ? (alpha) (0.05), thus the null hypothesis is rejected and there is a significant difference. The 10% concentration proved to be the most effective in replacing glacial acetic acid in the Turk solution.